Productivity effects of an exogenous improvement in transport infrastructure: accessibility and the Great Belt Bridge - Bruno L. De Borger; Ismir Mulalic; Jan Rouwendal (Tinbergen Institute, 2019)
Most studies of the effects of transport infrastructure on the performance of individual firms have focused on marginal expansions of the rail or highway network over time. In this paper, we study the short-run effects of a large discrete shock in the quality of transport infrastructure, viz. the opening of the Great Belt bridge connecting the Copenhagen area with a neighboring island and the mainland of Denmark. We analyse the effect of the opening of the bridge on the productivity of firms throughout the country using a two-step approach: we estimate firm- and year-specific productivity for a large panel of individual firms, using the approaches developed by Levinsohn and Petrin (2003) and De Loecker (2011). Then, controlling for firm-fixed effects, we relate productivity to a calculated measure of accessibility that captures the effect of the opening of the bridge. We find large productivity effects for firms located in the regions near the bridge, especially for relatively small firms in the construction and retail industry. Estimation results further suggest statistically significant but small positive wage effects throughout the country, even in regions far from the bridge. Finally, there is some evidence that the bridge has stimulated new activities in the Copenhagen region at the expense of firms disappearing on the neighboring island Funen.
Keywords: R12; H54; O18; 330; production functions; productivity; accessibility; agglomeration; transport infrastructure